Early feeds not force feeds: Enteral nutrition in traumatic brain injury. Issue 3 (September 2016) - Azim, Asad; Haider, Ansab A.; Rhee, Peter; Verma, Ket; Windell, Elizabeth; Jokar, Tahereh Orouji; Kulvatunyou, Narong; Meer, Mary; Latifi, Rifat; Joseph, Bellal
Abstract : BACKGROUND: Brain Trauma Foundation guidelines recommend the early use of enteral nutrition to optimize recovery following traumatic brain injury (TBI). Our aim was to examine the effect of early feeds (⩽24 hours) on clinical outcomes after TBI. METHODS: We performed a 3-year retrospective study of patients with severe TBI (Glasgow Coma Scale score <8) who were intubated, admitted to the intensive care unit (ICU), and received tube feeds. Early tube feeds (early TF) were defined as initiation of tube feeds within 24 hours, whereas late tube feeds (late TF) were defined as initiation of tube feeds after 24 hours. Outcome measures included pneumonia rates, days on ventilator, hospital and ICU stay, and mortality rates. RESULTS: A total of 90 patients (early TF: 58, late TF: 32) were included, of which 73.3% were male, mean age was 42 (SD, 20) years, and median head Abbreviated Injury Scale score was 4 (range, 3–5). There was no difference in age ( p = 0.1), head Abbreviated Injury Scale score ( p = 0.5), or admission Glasgow Coma Scale score ( p = 0.9) between the two groups. Patients with early TF were associated with higher number of ICU days ( p = 0.03) and higher pneumonia rates ( p = 0.04), but there was no significant difference in mortality ( p = 0.44) as compared with those who underwent late TF. CONCLUSIONS: Although early tube feeds are known to improve outcomes in TBI patients, our data suggest that early feeds in TBI patients are associated with higher rates of pneumonia and greater hospital resource utilization. LEVEL OF EVIDENCE: Therapeutic study, level IV.